MANAJEMEN PEMBELAJARAN DIGITAL DALAM RANGKA MENDUKUNG MERDEKA BELAJAR KAMPUS MERDEKA PASCA PANDEMI COVID-19 DI AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA - Susatyo Herlambang; Himawan Agung Nugroho; Sri Wahyuning (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2022)
This study aims to determine the method of digital learning transformation to support Merdeka Learning at the Merdeka Campus after the Covid-19 pandemic at the Yogyakarta Administrative Management Academy. This research method uses a qualitative approach. The number of respondents is 116 people, who are participating in teaching and learning activities using the digital learning transformation method. The results showed that 112 people (96.5%) supported, while 4 people (3.5%) did not support the implementation of digital learning transformation and Merdeka Learning Merdeka Campus. The challenges of digital learning transformation are weak internet signal, limited quota, smartphones or laptops that are not suitable for the application being operated, the ability to adapt to the presence of new technology, and the availability of existing memory.